Investigating PCK Among Malaysia Preschool Teachers in Early Mathematics - Seman, Norhaizian; Alias , Aliza; Ikhsan, Zanaton (International Journal of Psychosocial Rehabilitation, 2020)
This paper explored the Pedagogical Content Knowledge (PCK) of preschool teachers for preparing pupils to understand mathematical concepts. The main aspect being explored is student’s cognitive knowledge (SCK) and pedagogical knowledge (PK) by investigating, understanding and transforming classroom teaching practice in preschools. The design of this study was a case study with three preschool teachers who were selected as the research participants. Data were collected over five months in the form of interviews, teaching observation and document analysis. All of the interviews were in audio and video format while a checklist was used to record teaching observations. Analysis of the content of the documents produced was based on the teachers’ lesson plans and results were compared with previous research. Validity and reliability were established based on the Cohen Kappa Index Scale. This study found that the research participants possessed knowledge and understanding of student’s cognitive knowledge (PCK) in early mathematics. Furthermore, the research participants clearly demonstrated a good level of knowledge and understanding of pedagogical knowledge (PK) for early mathematics. It can be concluded that both PCK and PK are, therefore, important for helping preschool teachers to plan and conduct early mathematics activities that are relevant to their pupils’ stage of development and for enabling them to choose the best method of teaching practice. Selecting the best teaching practice in early mathematics is, of course, vital for making students' learning activities fun and meaningful for preschoolers.